Comparison of experimental fine‐mapping to in silico prediction results of HIV‐1 epitopes reveals ongoing need for mapping experiments - Roider, Julia; Meissner, Tim; Kraut, Franziska; Vollbrecht, Thomas; Stirner, Renate; Bogner, Johannes R.; Draenert, Rika (Immunology, 2014)
Summary Methods for identifying physiologically relevant CD8 T‐cell epitopes are critically important not only for the development of T‐cell‐based vaccines but also for understanding host–pathogen interactions. As experimentally mapping an optimal CD8 T‐cell epitope is a tedious procedure, many bioinformatic tools have been developed that predict which peptides bind to a given MHC molecule. We assessed the ability of the CD8 T‐cell epitope prediction tools syfpeithi, ctlpred and iedb to foretell nine experimentally mapped optimal HIV‐specific epitopes. Randomly – for any of the subjects' HLA type and with any matching score – the optimal epitope was predicted in seven of nine epitopes using syfpeithi, in three of nine epitopes using ctlpred and in all nine of nine epitopes using iedb. The optimal epitope within the three highest ranks was given in four of nine epitopes applying syfpeithi, in two of nine epitopes applying ctlpred and in seven of nine epitopes applying iedb when screening for all of the subjects' HLA types. Knowing the HLA restriction of the peptide of interest improved the ranking of the optimal epitope within the predicted results. Epitopes restricted by common HLA alleles were more likely to be predicted than those restricted by uncommon HLA alleles. Epitopes with aberrant lengths compared with the usual HLA‐class I nonamers were most likely not predicted. Application of epitope prediction tools together with literature searches for already described optimal epitopes narrows down the possibilities of optimal epitopes within a screening peptide of interest. However, in our opinion, the actual fine‐mapping of a CD8 T‐cell epitope cannot yet be replaced.